Analysis of the influence of greenwashing and well-to-wheel emissions on consumer preferences for BYD electric vehicles - Rohmatia, Prasastie Hutama; Diandra, Didip (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
The green economy programme reflects Indonesia’s commitment to renewable energy development and sustainable development in order to realise the Indonesia Emas 2045 vision. The purpose of this study is to analyse the influence of greenwashing and well-to-wheel (WTW) emissions on consumer preferences for BYD electric vehicles. This study uses quantitative descriptive analysis with purposive sampling, involving 120 respondents who are prospective users of BYD electric vehicles. Primary data was collected through a questionnaire distributed via Google Forms, and secondary data was obtained from a review of previous research literature. Data analysis was performed using SPSS version 25. The results of this study indicate that greenwashing has a significant negative effect on consumer preferences for electric vehicles, while well-to-wheel emissions have a significant positive effect on consumer preferences for BYD electric vehicles